2014
DOI: 10.3851/imp2940
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia is Associated with Monocyte Activation in HIV-Infected Adults on Antiretroviral Therapy

Abstract: Background Anemia has been linked with mortality in HIV infection. The mechanism of anemia in the era of contemporary antiretroviral therapy is not understood. The aim of this study was to describe the association between anemia and markers of immune activation and inflammation in a cohort of HIV-infected adults on stable antiretroviral therapy. Methods We performed a cross-sectional study of HIV-infected adults on antiretroviral therapy with HIV-1 RNA < 1000 copies/ml. Soluble and cellular markers of inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In the general population, anemia has been characterized as a risk factor for MI and HF. 910 Among PLHIV, anemia also has been shown to relate to accelerated HIV disease progression and increased systemic immune activation/inflammation, 111213 of relevance to HIV-associated CVD. Suppression of endogenous testosterone production may contribute to anemia among transgender women with HIV.…”
Section: Research Lettermentioning
confidence: 99%
“…In the general population, anemia has been characterized as a risk factor for MI and HF. 910 Among PLHIV, anemia also has been shown to relate to accelerated HIV disease progression and increased systemic immune activation/inflammation, 111213 of relevance to HIV-associated CVD. Suppression of endogenous testosterone production may contribute to anemia among transgender women with HIV.…”
Section: Research Lettermentioning
confidence: 99%
“…In fact, prevalence of anemia among HIV-infected patients is high [ 3 , 6 ] and it is frequently resolved after cART initiation [ 23 , 24 ]. Sometimes, however, anemia can persist in HIV-chronically-infected patients, even after HIV replication was suppressed with cART, and it has been associated with elevated levels of IL-6, CRP and D-dimer [ 3 ] and with monocyte activation [ 25 ]. This condition is considered as anemia of chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Kerkhoff et al found that the serum level of IL-6 was associated with the severity of ACD in patients with HIV and tuberculosis 20. In contrast, Lipshultz et al (2015) reported that IL-6 was not an independent predictor of anemia and mild anemia in HIV patients with cARV therapy 21. However, a study with fewer participants has concluded that serum IL-6 did not show significant correlation with anemia on PLWH on cARV therapy 22…”
Section: Discussionmentioning
confidence: 99%